Isolation And Characterization Of Marine Actinomycetes For Anti-Infective Activity Towards Pseudomonas aeruginosa PA14 - Kamal, Siti Nur Fatin Ahmad (2018)
Marine environment serve as reservoir of vast useful secondary metabolites and at the same time, new anti-infective agents are required to combat antibiotic resistant pathogenic bacteria.Therefore, this research was carried out to screen for anti-infective agents from the environment that are capable of overcoming Pseudomonas aeruginosa infection through anti-virulence or boosting of host immunity activities. Marine soil sediments were collected from Songsong Island, Yan, Kedah, Malaysia and a total of 18 actinomycetes with different morphology were successfully isolated. Secondary metabolites from all isolates were extracted out using solid-liquid extraction method and were screened for anti-infective activity using Caenorhabditis elegans infection model.